2011
DOI: 10.1177/097133361002300103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Islam on the Perceptions of Mental Illness of Volunteers in a Johannesburg Community-based Organisation

Abstract: Current understandings of mental illness are rooted in Western paradigms and fail to incorporate indigenous understandings. Swartz (2002) argues that the way certain conditions are labelled in different settings and how they are expressed in different cultures, need to be taken into consideration. Thus, this study explores the perceptions of mental illness in a sample of eight volunteer counsellors at a community-based organisation in Johannesburg, South Africa. Semi-structured interviews were conducted with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…A person in Islam is conceptualized as being the combination of four interacting parts, namely, mind (Aql), body (Qalb), self (Nafs), and soul/spirit (Ruh) (Laher & Khan, 2011). The person in Hinduism is conceptualized as five concentric layers, namely, the body, the 'breath of life' or physiological processes, the 'mind' or sensory function co-ordinator, the intellect and cognitive aspects of an individual, including self-image, and the jiva or the seat of experience of bliss (Paranjpe, 1998).…”
Section: Understanding the Origins Of Illness In Islamic Hindu And African Traditionsmentioning
confidence: 99%
“…A person in Islam is conceptualized as being the combination of four interacting parts, namely, mind (Aql), body (Qalb), self (Nafs), and soul/spirit (Ruh) (Laher & Khan, 2011). The person in Hinduism is conceptualized as five concentric layers, namely, the body, the 'breath of life' or physiological processes, the 'mind' or sensory function co-ordinator, the intellect and cognitive aspects of an individual, including self-image, and the jiva or the seat of experience of bliss (Paranjpe, 1998).…”
Section: Understanding the Origins Of Illness In Islamic Hindu And African Traditionsmentioning
confidence: 99%
“…Cultural competence refers to the ability to work within a community or culture that is different to one's own while maintaining a respect and understanding for that community and their cultural beliefs and practices (Bhui, Warfa, Edonya, McKenzie, & Bhugra, 2007;O' Hagan, 2001). According to Laher and Khan (2011), being aware and addressing cultural and religious beliefs is an important part of providing quality care to individuals with mental illness, as these aspects may provide a framework for understanding mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted that cultural competency puts patients at ease. [7] These ideas may be related to the concept of culture-matching as highlighted by Haarmans, [9] which refers to matching a clinician with a patient based on their racial/ ethnic identity. The belief is that this 'matching' will increase cultural competency and therefore therapeutic outcomes.…”
Section: Cultural Competencementioning
confidence: 99%
“…Laher and Khan [7] state that being aware of and addressing cultural and religious beliefs is an important part of providing quality care to individuals with mental illness, as these aspects may provide a framework for understanding mental illness. They found that patients were open to Western forms of treatment, but still preferred to be treated by someone they believed was competent in their understanding and knowledge of their culture.…”
Section: Cultural Competencementioning
confidence: 99%
See 1 more Smart Citation